Mail Response Rate Patterns in a Population of Elderly: Does Response Deteriorate With Age? - Kaldenberg,Dennis O.; Koenig,Hal; Becker ,Boris W. (Public Opinion Quarterly, 1994)
The article presents information on a study conducted by the researchers to examine whether the rate and quality of response to a mail survey, directed to the elderly, is in any way affected by the age of the potential respondent. Quality of the responses, in this context, is defined as the percent of missing responses to different question formats and the extent to which the questionnaires for given age groups are completed by a proxy. In this study a random sample of size 1,000 was drawn from a population of 23,000 retired public employees in the files of an insurance services provider based in a large western city. The results of this study indicated that age, within an elderly population, does have a significant impact on response rate to a mail questionnaire. On average, the response rate fell more than 0.5 percentage points for each unit of measure of age. The influence of age on response quality is less clear. For four of the five question formats, a significant positive relationship was found between age and amount of missing data.
Keywords: Marketing